(untitled) (Journal of history, 2019)
The article highlights the results of a study on the epigraphy of the Syr Darya land (on Shieli and Zhanakorgan regions). The study of the epigraphy of the Syr Darya land became possible during the implementation of the scientific project «Epigraphy of the region: spiritual modernization and continuity of generations». The main purpose of the study of the epigraphy of the land of Syr Darya was the disclosure of new sources related to the history of the region and national historiography, as well as their inclusion in scientific circulation. In the course of research, the methods of field research were used: field exploration, fixation, accounting of epigraphic materials and the collection of oral materials. The inscriptions in Arabic fixed epigraphic heritage were translated into Kazakh. According to the research results, the epigraphic heritage of the land of Syr Darya (Shieli and Zhanakorgan regions) is mainly the inscriptions on the tombstones. Most of them are localized in the early cemeteries, including the burial grounds where the holy people are buried. Information in tombstones contains data such as name, gender, year of death of the buried. In addition, the verses of the Koran were carved in the tombstones. The collected epigraphic materials will certainly contribute to the completion of data on the location of the living in the Syr Darya region in the early XIX century-XX century.